A risky proposal: turning repositories into mega-journals - Ortega, José-Luis (Anuario ThinkEPI, 2022)
The aim of this communication is to consider the new problems that open-access models are posing for scholarly communication. Double charging, publishers with nonstandard practices, and biases associated with accessing the publishing market are some of the recent problems that the pay-to-publish model is producing. Taking these problems into account, this paper presents a proposal for combining the green and gold models, proposing a solution that could benefit the publishing system, separating it from the commercial sector. The article suggests the creation of journals through repositories, which would permit articles reviewed through open access, whose evaluation process would be supported by the same entities that fund them, to be published removed from commercial interests. The proposal is set out as a debatable idea that discusses the commercial nature of scientific publishing.